Heads, Bodies, Brains, and Selves: Personal Identity and the Ethics of Whole-Body Transplantation. Issue 2 (11th May 2022) - Iltis, Ana
Abstract: Plans to attempt what has been called a head transplant, a body transplant, and a head-to-body transplant in human beings raise numerous ethical, social, and legal questions, including the circumstances, if any, under which it would be ethically permissible to attempt whole-body transplantation (WBT) in human beings, the possible effect of WBT on family relationships, and how families should shape WBT decisions. Our assessment of many of these questions depends partially on how we respond to sometimes centuries-old philosophical thought experiments about personal identity. As with so much in bioethics, it is impossible to escape, or at least inadvisable to try to bypass, the relevant foundational philosophical concerns.